The Probe Team [episode no. 309] (Probe Productions, 1994)
The first part is an arguement between Church and State on the document presented at the International Conference on Population and Development in Cairo. The second part is about the recent study for the mentally ill not to be institutionalized. The last part is a play written in 1901 on fight against this Spanish colonizers.